Convergence of Accounting to IFRS in India: An Empirical Study - Vasudeva, Sakshi; Singh, Preeti (Gyan Management Journal, 2012)
In view of liberalization and globalization of economies, the convergence of accounting standards is the need of the hour today, but there are various challenges that need to be overcome for smooth transition to IFRS. In the present paper, an empirical study was conducted to know the opinion of real implementers of convergence, that is chartered accountants. The results of the empirical study revealed that the accountants support convergence as it will lead to greater transparency and reliability. The major challenges are training requirements of accountants and issues related to differences in economic conditions and socio-political environment of the country.